Corticosteroid injection prior to surgery had no effect on 2-year outcomes following arthroscopic rotator cuff repair - Smith, Justin T (JSES international, 2024)
© 2023 Published by Elsevier Inc. on behalf of American Shoulder and Elbow Surgeons.